2011
DOI: 10.1080/10510974.2011.582663
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Work/Life Blending: Credibility Implications for Those Who Date at Work

Abstract: This study examined the credibility implications of employees who date at work. A 2 (status dynamic of the romance) Â 2 (sex of the peer) design was used to examine effects of workplace romance on perceptions of credibility. One hundred and forty full-time working adults assessed the credibility of a hypothetical coworker who was involved in a workplace romance. Results indicate that peers who date superiors are viewed as less caring and less trustworthy than are peers who date equal status employees. Sex and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(92 citation statements)
references
References 58 publications
5
82
2
3
Order By: Relevance
“…Furthermore, discourses of sexuality may aid in generating and upholding organizational values and identities (Tracy & Scott, 2006). Even so, empirical research shows that third parties have relatively negative reactions to WR and their coworkers who engage in them (Dillard et al, 1994;Horan & Chory, 2009, 2011Pierce, 1998). The present study further examines the tensions associated with the public (work)-private (sexuality) split through its study of WRs.…”
Section: The Public-private Spheres Of Work and Sexualitymentioning
confidence: 81%
See 2 more Smart Citations
“…Furthermore, discourses of sexuality may aid in generating and upholding organizational values and identities (Tracy & Scott, 2006). Even so, empirical research shows that third parties have relatively negative reactions to WR and their coworkers who engage in them (Dillard et al, 1994;Horan & Chory, 2009, 2011Pierce, 1998). The present study further examines the tensions associated with the public (work)-private (sexuality) split through its study of WRs.…”
Section: The Public-private Spheres Of Work and Sexualitymentioning
confidence: 81%
“…However, the empirical evidence on the topic is mixed. Horan and Chory (2011) found that heterosexual women dating superiors versus peers were seen as less caring and less trustworthy by coworkers, whereas perceptions of heterosexual men did not differ based on the status of their partner. Furthermore, Horan and Chory (in press) reported that employees perceived homosexual female coworkers in WRs to be less competent and caring than they perceived homosexual male coworkers in WRs, and employees were more likely to deceive homosexual female versus homosexual male coworkers involved in WRs.…”
Section: Sex Of the Individual Involved In A Workplace Romancementioning
confidence: 88%
See 1 more Smart Citation
“…In Sweden in 2012 men who were business economists, in marketing, or human resources officers had an average monthly salary of 45 400 Swedish crowns and women in the same professions earned almost 9 000 Swedish crowns less per month (Statistics Sweden, 2012). Horan and Chory (2011) found in a survey study presenting four fictitious scenarios that respondents viewed the trustworthiness and goodwill of men in a workplace romance more positively than that of women, and they viewed women who dated superiors as less caring and trustworthy than women who dated equals. Yet their perceptions of men's did not change based on the work status of their partners.…”
Section: Gender and Workplace Romancesmentioning
confidence: 99%
“…Most empirical studies on workplace romance (e.g., Anderson & Fisher, 1991;Brown & Allgeier, 1996;Horan & Chory, 2011;Mainiero, 1986;Powell, 2001;Quinn, 1977) have relied mainly on data from co-workers' observations and self-report surveys (Wilson, 2015), which can provide useful knowledge on organization morale and equitable employee treatment (Cowan & Horan, 2014;Liberman & Okimoto, 2008;Pierce & Aguinis, 2009). However, it is also important to conduct interviews and discussions with people who have experienced workplace romance to supplement the largely third-person perspective of previous research with first-person perceptions.…”
Section: Summary and Aimmentioning
confidence: 99%